Engaging stakeholders in rehabilitation research: a scoping review of strategies used in partnerships and evaluation of impacts. (July 2015) - Camden, Chantal; Shikako-Thomas, Keiko; Nguyen, Tram; Graham, Emma; Thomas, Aliki; Sprung, Jennifer; Morris, Christopher; Russell, Dianne J.
Abstract Purpose: To describe how stakeholder engagement has been undertaken and evaluated in rehabilitation research. Methods: A scoping review of the scientific literature using five search strategies. Quantitative and qualitative analyses using extracted data. Interpretation of results was iteratively discussed within the team, which included a parent stakeholder. Results: Searches identified 101 candidate papers; 28 were read in full to assess eligibility and 19 were included in the review. People with disabilities and their families were more frequently involved compared to other stakeholders. Stakeholders were often involved in planning and evaluating service delivery. A key issue was identifying stakeholders; strategies used to support their involvement included creating committees, organizing meetings, clarifying roles and offering training. Communication, power sharing and resources influenced how stakeholders could be engaged in the research. Perceived outcomes of stakeholder engagement included the creation of partnerships, facilitating the research process and the application of the results, and empowering stakeholders. Stakeholder engagement outcomes were rarely formally evaluated. Conclusions: There is a great interest in rehabilitation to engage stakeholders in the research process. However, further evidence is needed to identify effective strategies for meaningful stakeholder engagement that leads to more useful research that positively impacts practice. Implications for Rehabilitation Using several strategies to engage various stakeholders throughout the research process is thought to increase the quality of the research and the rehabilitation process by developing proposals and programs responding better to their needs. Engagement strategies need to be better reported and evaluated in the literature. Engagement facilitate uptake of research findings by increasing stakeholders' awareness of the evidence, the resources available and their own ability to act upon a situation. Factors influencing opportunities for stakeholder engagement need to be better understood.